2009
DOI: 10.1038/onc.2009.453
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activity of the CREB co-activator Crtc1 in LKB1 null lung cancer

Abstract: Activation of Crtc1 (also known as Mect1/Torc1) by a t(11;19) chromosomal rearrangement underlies the etiology of malignant salivary gland tumors. As LKB1 is a target for mutational inactivation in lung cancer and was recently shown to regulate hepatic Crtc2/CREB transcriptional activity in mice, we now present evidence suggesting disruption of an LKB1/Crtc pathway in cancer. Although Crtc1 is preferentially expressed in adult brain tissues, we observed elevated levels of steadystate Crtc1 in thoracic tumors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…As SIKs enzymatic activities are dependent on LKB1, it is anticipated that LKB1 deregulation impacts CRTC1 functional activities. This is supported by a recent study that indicated somatic loss of LKB1 in lung cancer is associated with CRTC1 activation (Komiya et al, 2010). However, questions still remain regarding the exact functional consequences of CRTC activation in tumorigenesis and whether CRTC activation is a key mediator in LKB1 loss.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…As SIKs enzymatic activities are dependent on LKB1, it is anticipated that LKB1 deregulation impacts CRTC1 functional activities. This is supported by a recent study that indicated somatic loss of LKB1 in lung cancer is associated with CRTC1 activation (Komiya et al, 2010). However, questions still remain regarding the exact functional consequences of CRTC activation in tumorigenesis and whether CRTC activation is a key mediator in LKB1 loss.…”
Section: Introductionmentioning
confidence: 63%
“…Conversely, LKB1 knockdown in LKB1-expressing KYSE-70 cells led to a significant LYPD3 upregulation (Figure 5b). We also determined another target gene, NR4A2, in parallel, which is critical for the growth of lung cancer cells (Komiya et al, 2010). We found that NR4A2 shows similar changes in response to LKB1 modulation, but its expression is generally lower compared with LYPD3 (Supplementary Figure 9).…”
Section: Deregulated Lkb1-crtc Signaling In Esophageal Cancermentioning
confidence: 90%
See 1 more Smart Citation
“…We previously showed that loss of LKB1 expression resulted in dephosphorylation and nuclear entry of CRTC transcriptional coactivators and subsequent CREB-mediated transcriptional activation in both lung and esophageal cancer cells (41,42). LINC00473 was transiently upregulated in response to cAMP signaling in human ocular ciliary smooth muscle cells (43).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of CREB by CRTCs is harnessed by CRTC phosphorylation, which retains these coactivators in the cytoplasm (46). Therefore, constitutive CREB activity is manifest following inactivation of upstream regulatory kinases such as LKB1 that phosphorylate CTRCs (47)(48)(49). Indeed, several human esophageal tumor cell lines express reduced levels of LKB1 and CRTC1 phosphorylation relative to Het1 immortalized, normal esophageal epithelial cells (48).…”
Section: Tetomentioning
confidence: 99%